2020
DOI: 10.1016/s2542-5196(20)30058-9
|View full text |Cite
|
Sign up to set email alerts
|

Health impact assessment of Philadelphia's 2025 tree canopy cover goals

Abstract: Background Cities across the world are undertaking ambitious projects to expand tree canopy by increasing the number of trees planted throughout public and private spaces. In epidemiological studies, greenspaces in urban environments have been associated with physical and mental health benefits for city dwellers. Greenworks Philadelphia is a plan to increase tree cover across Philadelphia (PA, USA) by the year 2025. We aimed to assess whether an increase in tree canopy or greenspace in Philadelphia could decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 37 publications
2
42
0
3
Order By: Relevance
“…To do so, we modelled the association between the %GA and NDVI for each city and established the target NDVI as the NDVI value associated to 25%GA (ie, target for %GA analysis), based on a similar approach of a health impact assessment green space study for the city of Philadelphia. 26 Most of the cities (768 [89%] of 866) showed strong non-linear correlation (Spearman ρ>0•7) between %GA and NDVI, and only 12 cities showed non-linear correlations with Spearman ρ<0•4 (figure 2). To allow for non-linear relationships, we used a generalised additive model (GAM) employing the grid-cell level %GA as predictor variable and the grid-cell level NDVI as the outcome variable.…”
Section: Counterfactual Levels Of Exposure To Green Spacementioning
confidence: 98%
See 1 more Smart Citation
“…To do so, we modelled the association between the %GA and NDVI for each city and established the target NDVI as the NDVI value associated to 25%GA (ie, target for %GA analysis), based on a similar approach of a health impact assessment green space study for the city of Philadelphia. 26 Most of the cities (768 [89%] of 866) showed strong non-linear correlation (Spearman ρ>0•7) between %GA and NDVI, and only 12 cities showed non-linear correlations with Spearman ρ<0•4 (figure 2). To allow for non-linear relationships, we used a generalised additive model (GAM) employing the grid-cell level %GA as predictor variable and the grid-cell level NDVI as the outcome variable.…”
Section: Counterfactual Levels Of Exposure To Green Spacementioning
confidence: 98%
“…We performed the analysis by city and greater city. We followed the Urban and Transport Planning Health Impact Assessment methodology, [21][22][23][24][25][26] based on the comparative risk assessment approach in relation to a counterfactual scenario. 27 We defined our counterfactual scenario as compliance with the WHO recommendation of universal residential access to green space, because it is the only internationally recognised recommendation, and retrieved exposureresponse functions from the literature, quantifying the strength of association between exposure to green space and mortality.…”
Section: Quantitative Health Impact Assessmentmentioning
confidence: 99%
“…What else these new urban models share to some extent is improving access to green space, which is important for, for example, peoplés mental health, cognitive functioning and life expectancy ( Gascon et al, 2015 , Kondo et al, 2020 ). The availability of green space varies quite considerably between cities and is also not equally distributed within cities, with some people having easy access to green space, while others have not ( Schüle et al, 2017 , Pereira Barboza et al, 2021 , Mushangwe et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in early childhood this may be important as a recent study showed that children who went to a school with more green spaces had considerably better cognitive functioning than those who went to a school with less green spaces ( Dadvand et al, 2015 ), while another study found that early child hood exposure to green spaces leads to fewer mental health problems in adult life ( Preuß et al, 2019 ). Multiple studies have found that green space reduces premature mortality ( Rojas-Rueda et al, 2019 ), and increasing tree canopy from 20% to 30% in a city such as Philadelphia could prevent more than 400 premature deaths annually ( Kondo et al, 2020 ). Particularly, poorer neighbourhoods would benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Eliminating the inequitable distribution of trees seen in many urban areas can also help remedy current health inequities resulting from racist laws and policies. 26 Historic redlining practices have made many low-income communities and communities of color more susceptible to extreme heat and flooding due to concentrated areas of hot impervious surface and limited tree cover: historically redlined neighborhoods (deemed hazardous for real estate investments in the 1930s based on racial makeup of the neighborhood) are, on average, 5 degrees hotter than neighborhoods with higher percentages of white residents. 27 Increasing urban tree cover, particularly in formerly redlined neighborhoods, areas with high asthma rates, and near schools in low-income communities of color, can promote health equity while simultaneously providing climate adaptation and climate mitigation benefits.…”
Section: The Power To Change the Natural Environment As A Means mentioning
confidence: 99%